RADIATION THERAPY FOR ENDOMETRIAL STROMAL SARCOMA: A LITERATURE REVIEW - Kusumaningrum, Nadia Nita; Dyarma, Kadiota Rasika; Nugroho, Rafiq Sulistyo; Petrarizky, Alfred Julius (International Journal of Radiology and Imaging, 2024)
Background: Endometrial Stromal Sarcoma (ESS) is a part of uterine sarcoma that can clinically manifest with abnormal vaginal bleeding, postmenopausal bleeding, uterine enlargement or mass, dysmenorrhea, pelvic pressure, or pain. ESS is divided into four main categories: endometrial stromal nodule, low-grade ESS, high-grade ESS, and undifferentiated uterine sarcoma. Management for ESS includes surgery, chemotherapy, radiotherapy, and hormone therapy. We want to review the role of radiation therapy for endometrial stromal sarcoma, from several pieces of literature. Material and Methods: We are conducting a literature review to describe the role of radiation therapy for ESS. Results: Radiotherapy serves as an adjuvant treatment in ESS, potentially improving prognosis and survival rates. While early-stage ESS may not necessitate radiotherapy, it can be considered for ESS cases with metastasis or when surgery is not an option. Conclusion: According to previous studies, radiotherapy for ESS can improve disease-free survival and increase patient survival. On the other hand, there are studies that still require large-scale prospective studies to validate the effectiveness of radiotherapy for ESS. Keywords: Endometrial Stromal Sarcoma, Radiotherapy, Effectiveness